∫2x(x+2)^(1/2) dx evaluated from 0->2

First make a substitution so we can apply the power rule ∫xn dx = (xn+1)/(n+1) + C more simply. Can see u=x+2 means (x+2)1/2 -> u1/2 and so will help us apply this rule. Change dx/du=1 implies dx = du, and x=0 => u=2, x=2 => u =4 so we now integrate from 2 -> 4.
x=u-2 gives ∫2x(x+2)1/2 dx = ∫2(u-2)(u)1/2 dx = 2∫u3/2 du - 4 ∫u1/2 du. We can now apply the power law above with the new integration limits to obtain the answer (32)/(15) ( 2 + (2)^(1/2) ).

Answered by Luke P. Maths tutor

10481 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Show that the cubic function f(x) = x^3 - 7x - 6 has a root x = -1 and hence factorise it fully.


A curve has an equation: (2x^2)*y +2x + 4y – cos(pi*y) = 17. Find dy/dx


How do I find the equation of the tangent to y = e^(x^2) at the point x = 4?


How to do the product rule for differentiation


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences